Shape matters: gold nanoparticle shape impacts the biological activity of siRNA delivery - Morgan, Erin; Wupperfeld, Dominik; Morales, Demosthenes; Reich, Norbert (Bioconjugate chemistry, 2019)
Plasmon-resonant nanoparticles provide unprecedented spatiotemporal control over the release of diverse cargoes into cells. Here we compare the loading, release and internalization efficiencies, and effectiveness of post transcriptional gene silencing of hollow gold nanoshells, hollow gold nanocages, and gold nanorods with plasmons tuned to absorb near-infrared light at 800 nm. The hollow gold nanoshells can be loaded with up to three times more siRNA cargo compared to nanocages and nanorods; however, nanorods exhibit the highest efficiency of release of attached siRNA strands when exposed to pulsed 800 nm laser excitation. In cellular treatments, all particles demonstrated efficient internalization into HeLa cells, but the nanoshells and nanocages display the highest downregulation of GFP expression 72 h after treatment. These results provide novel insights into the relative efficiencies of three structurally distinct types of gold nanoparticles as siRNA carriers and we examine different parameters that may influence their efficacy.
Gesehen am 13.06.2019